The Effect of Gargling with Lemon Water (Citrus limon I) on Debris Index and Saliva pH in Students of SDN 12 Banda Aceh City, Indonesia - Reca RECA; Citra Feriana PUTRI (Dentistry Faculty, 2021)
ABSTRACT Control of debris or plaque is an effort to prevent plaque buildup. These efforts can be mademechanically or chemically. Getting rid of dental plaque and neutralizing the pH of saliva from the tooth surface isdone by brushing your teeth and gargling. Herbal mouthwash that can be used is lemon juice, a bright yellow fruitknown to have an acidic taste. This study aims to determine the effect of rinsing lemon water (Citrus Limon L) onthe debris index and salivary pH in fifth-grade students of SDN 12 Banda Aceh City. This type of research is quasiexperimental.The subjects in this study were all Class V students of SDN 12 in Banda Aceh City, totaling 60children, then divided into two groups, the intervention group consisted of 30 children given intervention (garglingwith lemon juice), and the control group consisted of 30 children who were not given intervention (gargling withwater). Analysis of data results (quantitative) in this study using; using the non-parametric (Wilcoxon) and MannWhitney. The results of the study show. There was no difference in the mean value of acidity of saliva (salivary pH),and index debris means statistically significant values (p 0.05) in the control group (rinsing with water before andafter the intervention. There was a mean difference in the value of acidity of water saliva (salivary pH), and indexdebris means were statistically significant (p 0.05) in the treatment group (rinsing with lemon juice) before andafter the intervention. There was no significant difference between the treatment and control groups in pH Salivaand index debris before intervention ( pre-test). It was shown p statistically 0.05. There was a significant differencein the Saliva pH and index debris after the treatment (post-test) between the treatment and control groups. p 0.05,which means that gargling with lemon juice containing 10% citric acid can cause changes in the pH of the saliva andthe debris index. San lemon can be used as an alternative mouthwash to overcome dental and oral health problems. KEYWORDS: Lemon Water Gargle, Debris Index, Saliva pH